EVALUATION OF THE USE OF SHARED DECISION MAKING DURING ANTENATAL COUNSELLING FOR ANTICIPATED EXTREMELY PRETERM BIRTH. (18th May 2018) - Ding, Sharon; Bijelic, Vid; Daboval, Thierry; Lemyre, Brigitte; Dunn, Sandra; Moore, Gregory
Abstract: BACKGROUND: Paediatric organizations advocate the use of shared decision making (SDM) during counselling with families facing the birth of an extremely preterm infant. A local guideline was implemented in 2015 to promote SDM. OBJECTIVES: To determine the percentage of consultations where SDM was used. DESIGN/METHODS: Single-center prospective cohort study from September 2015 to June 2017 with data collected on all women presenting to obstetrical triage at 22 + 0 to 25 + 6 wks GA. Decision coaching (determined from the written consultation) during consultations served as a surrogate marker for use of SDM. Fisher's exact test was used to compare proportions; logistic regression was used to examine trend over time. RESULTS: 130 women presented. A neonatology consultation occurred in 92 cases. SDM was used at initial consultation in 85% (78/92) of cases: 84% (16/19) at 22 wks; 88% (22/25) at 23 wks; 96% (27/28) at 24 wks; 65% (13/20) at 25 wks. Secondary analyses indicate use of SDM declined over time (p=0.03) and parental ability to come to a decision was not significantly different between SDM and 'non-SDM' consults (89% in SDM vs 92% in non-SDM; p=0.7). At 22 wks, 89% (17/19) made a decision; at 23 wks, 80% (20/25); at 24 wks, 86% (24/28); at 25 wks, 85% (17/20) (p=0.84). Infant survival to NICU discharge, using denominator 'infants who received resuscitation', was 67% (2/3) at 22 wks; 33% (3/9) at 23 wks; 87% (13/15) at 24 wks; 89% (17/19) at 25 wks. CONCLUSION: Implementation of an SDM framework is feasible with a resulting high percentage of consultations appearing to use SDM. The possible waning use of SDM and lower use at 25 wks GA requires further investigation. Recordings of consultations and parental perspectives to directly assess the use of SDM would provide greater insight into the applicability of SDM in this clinical setting.